Redical Muslim fringe groups' recourse to Takfīr (accusing Muslims of infidelity) a critique - Ushama, Thameem (Hamdard Foundation Pakistan, 2016)
This paper analyses dogmatic extremism with a special focus on legal rulings regarding the matter of accusing other Muslims of being infidels. It defines the Arabic term according to the Qur'ān, Hadïth literature, and traditional Islamic dialogues. The study employs a qualitative content analysis of relevant literature referring to issues relating to unbelief (kufr), polytheism (shirk), faith (īmāri), accusing Muslims of infidelity (takfir), and legal injunctions holding societal implications. The scope is limited to the issue of takfir advocated by organizations or individuals without focussing on their historical background. It attempts to correct misconceptions of Islam as an unjust immoderate religion. It considers accusations of unbelief made in respect of (i) Individuals who are guilty of acts of sin and disobedience; (ii) Rulers who do not base their policies and judgements on the Sharl'ah; (iii) The subjects of such rulers who continue to accept the authority of a ruler who conducts himself in this way; (iv) and individuals who leave or withdraw from Islamic organizations. The paper also includes scholarly critiques of extremist views on accusing Muslims of infidelity and provides intelligent responses based on solid evidence from the Sunnah, as well from the exegetes.